Taṭwir Kitab Khulāșah Nūr al-Yaqīn bi al-Șuwar al-Bayāniyah - Mayumi Maysah; Mukhlisah Mukhlisah (DAYAH: Journal of Islamic Education, 2018)
The book hold the most crucial part in learning process which contain knowledges, and ideas in certain things. It main source of knowledge used by teacher and students. Khulashah Nurul Yaqin book is one of the books which is used at DarulUlum Islamic Boarding School to enhance students' reading skills. The book consists of three volumes, which is printed on opaque papers. It contains a collection of passages that narratethe history of Prophet Muhammad (peace be upon him), as well as questions about the passages. An uninteresting book may be a reason that makes students demotivated in learning. This problem may be solved by using pictures to trigger students' motivation. Therefore, the writer wants to develop Khulashah NurulYaqin book with pictures. The purpose of this research is to find out about the development process of utilizing pictures in Khulashah Nurul Yaqin book, research obstacles, and the results of using pictures to develop Khulashah Nurul Yaqin book. This study uses the Research and Development method as its research method. Tests, questionnaires, and interviews are research instruments used to obtain the research data, while T-Test Related is used as an instrument to analyse the obtained data. This study is conducted in accordance to the determined measures in this research and development method. The result of this study shows that using pictures to develop KhulasahNurulYaqin book is effective to increase students' comprehension in Tarikh learning.